Analysis of a Construction Company’s Strategy with Allowance for Risk - Vladimir Viktorovich BREDIKHIN; Natalia Vladimirovna BREDIKHINA; Anna Ilinichna CHERNYAEVA (Communications of International Proceedings, 2020)
Due to their complexity and longtermness, construction activities require a scientific approach to strategic management. To form and implement an effective strategy of a construction organization, a special place is given to the analysis of the macro environment and internal environment of a construction organization, identifying the risks faced by construction sector companies. The paper deals with strategies based on the analysis of management decisions with allowance for risk. The results of the study can be used by managers of construction organizations to plan their activities.
Keywords: Construction sector; construction company; management; strategy; risk.